Relationship Between Husband's Support And Mother's Compliance In First Trimester Pregnancy Examination In Practicing Midwives Independent Kartika, Timang Gajah District Bener Meriah District - Hudnah, Hudnah; Arami, Nova; HS, Nurlaely (Jurnal Maternitas Kebidanan, 2025)
Maternal Mortality Rate (MMR) is one of the development targets. Efforts to reduce MMR (pregnancy, childbirth, and postpartum) need quality Ante Natal Care (ANC) services according to government policy standards, namely at least 4 times during pregnancy, 1 time in the first trimester, 1 time in the second trimester, and 2 times in the third trimester. The husband's support is very much needed in the implementation of pregnant women's compliance in Antenatal Care (ANC) examinations. Being accompanied by a husband in conducting the examination can increase the motivation of pregnant women to check their pregnancy. The purpose of this study was to determine the relationship between a husband's support and maternal compliance in first-trimester pregnancy check-ups at the Midwife Kartika Clinic, Timang Gajah District, Bener Meriah Regency. This research method is analytically descriptive with a cross-sectional design. Total population of 51 respondents with a total sample of 33 respondents. This research was conducted at the clinic of Kartika midwives from 13 to 18 October 2024. The Chi-Square test result (p-value = 0.004 < 0.05) indicates a significant relationship between the husband's support and maternal compliance in first-trimester pregnancy check-ups at the Midwife Kartika Clinic, Timang Gajah District, Bener Meriah Regency. Mothers who received support from their husbands were 80% more likely to comply with pregnancy check-ups. With this research, it is expected that the knowledge of the husband or family about maternal support during pregnancy can be increased by the existence of this research and knowing the importance of pregnancy visits. Keywords: Husband Support, Maternal Compliance, Pregnancy Test Trimester I